2018
DOI: 10.1007/s41547-017-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for using a double-wavelength (940 nm + 2780 nm) laser in endodontics: literature overview and proof-of-concept

Abstract: Aim The goal of endodontic research is to report interventions, techniques or protocols that are most likely to deliver the outcomes that are of most interest to both clinicians and patients. The development of a double-wavelength laser delivered concomitantly and through the same radial firing tip (RFT) may provide a unique combination of beneficial properties that may clinically surpass all previously reported laser-assisted protocols. The aim is to present a rational literature overview that could support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 123 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…The success of endodontic treatment depends ultimately on the elimination of the microorganism, host response, and coronal seal of root canals [ 22 ]. Achieving long-term successful endodontic treatment without toxic chemical irrigants has always been a long-awaited goal of scientists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of endodontic treatment depends ultimately on the elimination of the microorganism, host response, and coronal seal of root canals [ 22 ]. Achieving long-term successful endodontic treatment without toxic chemical irrigants has always been a long-awaited goal of scientists.…”
Section: Discussionmentioning
confidence: 99%
“…further in vivo research used 2780 and 940 nm wavelengths for smear layer removal and achieved deep dentin disinfection respectively on two cases of relatively high endodontic complexity. Their 1-year follow-up supported the effectiveness of this treatment strategy [ 22 ].…”
Section: Introductionmentioning
confidence: 89%
“…15,16 In 2018, Martins et al reported the reduction of the bacterial count in deep layers of the infected root canal wall up to 74% by means of the diode laser (810 nm). 19 In 2018, Tilakchand et al performed an in vivo study in order to evaluate the antibacterial effect of the diode laser on the infected root canal wall. The laser used in this study was EZLASE diode laser (940 nm).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, near infrared range diode lasers (810, 940, 980 nm) and Nd: YAG laser (1064 nm) are mostly absorbed by hemoglobin and melanin [28] and their disinfection is even deeper (Gutknecht 2008). Therefore, in a recent study of Martins et al (2018) [29], it is suggested the double-wavelength application (erbium and diode laser) for a better outcome of the endodontic therapy as each laser wavelength has a specific absorption coefficient in every tissue [30].…”
Section: Discussionmentioning
confidence: 99%